Writing Strategies for Effective Learning - Avila Andrea Tatiana (2019)
This strategy can be used from beginners to intermediate students. The materials that the teacher needs in advance is“ My Friendly Sentence” template that is attached in Figure 2. This template can be drawn either in paper chart or on the board. As a first step, the teacher writes down the title “Lifestyle” in the circle and show a picture. The teacher asks students to describe the picture and writes down all the students’ ideas on the board.